2008
DOI: 10.1111/j.1460-9592.2008.02555.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypersensitivity reaction on re‐exposure to basiliximab in an infant undergoing heart transplantation

Abstract: after the administering of insulin, unlike the glucose response, which requires 30-60 min. The marked resistance of the glycemic metabolism to insulin makes the coadministering of glucose unnecessary and it is better to monitor glycemia at 30-min intervals (4). Here, the greater need for glucose after reperfusion, even with good signs of the functioning of the graft was attributed to the longer plasma half-life of the insulin because of CRI.TEG measures the viscoelastic and mechanical properties of the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…We had 1 case of severe anaphylaxis in a 14-monthold child given basiliximab previously at an aborted transplant-an experience reported previously 21 and common to other findings in solid-organ transplantation. 22 This reinforces the importance of delaying basiliximab until it is certain that the donor organ is suitable to avoid the risk of sensitization and anaphylaxis at subsequent transplant.…”
Section: Limitationssupporting
confidence: 51%
“…We had 1 case of severe anaphylaxis in a 14-monthold child given basiliximab previously at an aborted transplant-an experience reported previously 21 and common to other findings in solid-organ transplantation. 22 This reinforces the importance of delaying basiliximab until it is certain that the donor organ is suitable to avoid the risk of sensitization and anaphylaxis at subsequent transplant.…”
Section: Limitationssupporting
confidence: 51%
“…The low infection and malignancy rates are particularly important as there was a double total dose of daclizumab administered for 4 months longer in the SF than the steroid-based protocol, with equivalent dosing for tacrolimus and MMF in the two treatment arms. Furthermore, given some recent concerns of hypersensitivity with chimeric monoclonal interleukin 2 receptor antibody (basiliximab) infusions (32;33), it is important to note that there were no infusion-related adverse events with the fully humanized daclizumab in either treatment arm. The results of the current study can however not be generalized, and as daclizumab has been withdrawn from the market, it will be necessary to separately evaluate the safety and efficacy of basiliximab for induction in steroid-free immunosuppressive regimens in pediatric kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, some case studies reported anaphylactic reactions after exposure to basiliximab. [9][10][11] These reactions were reported both on initial exposure to basiliximab and on reexposure. 11 According to the Novartis product prescribing information, other acute hypersensitivity reactions have been reported in patients treated with basiliximab.…”
Section: Discussionmentioning
confidence: 99%